Pemanfaatan Limbah Kopi sebagai Vermikompos untuk Intercropping Cabai dan Bawang Merah oleh Kelompok Tani Hortikultura di Timang Gajah-Bener Meriah - Halimursyadah, Halimursyadah; Zulwanis, Zulwanis; Indra, Indra; Jauharlina, Jauharlina; Afrina, Nyak Yusfa (Universitas Syiah Kuala, 2023)
The processing of coffee cherries yields unused fruit skin waste, which can be transformed into valuable vermicompost. Vermicompost, which is generated through the process of introducing earthworms such as Eisenia foetida, incorporates vital macro- and micronutrients alongside plant growth regulators. A pre-survey revealed several issues faced by partners: (1) Neglected potential of coffee pod waste area, (2) Fertilizer challenges among horticultural, chili, and shallot farmers, (3) Limited knowledge about coffee pod skin composting as organic fertilizer, and (4) Inadequate cultivation management leading to unprofitable outcomes. To address these challenges, the Community Service Team collaboratively agreed with partners to: (1) Provide counseling on utilizing Eisenia foetida-inoculated coffee waste as vermicompost organic fertilizer, (2) Enhance horticultural farmers' understanding to reduce excessive inorganic fertilizer use, (3) Pilot coffee waste vermicompost application in intercropped chili and shallot cultivation, and (4) Establish coffee waste vermicompost packaging as a farmer group business venture. The achieved outcomes include: First, partner farmer groups received counseling on vermicompost production using Eisenia foetida worm inoculation. Second, partners significantly improved their vermicompost production proficiency. Third, demonstration plots successfully showcased chili and shallot cultivation using vermicompost. Fourth, partners effectively produced vermicompost, leading to a 20% reduction in production costs. Finally, partners were inspired to actively produce and apply vermicompost in their intercropped chili and shallot cultivation, reflecting positive motivation and progress.